FEATURES OF DIGITAL TRANSFORMATION OF THE TRANSPORT SPHERE IN MODERN CONDITIONS - Abdullaeva M. N. (Ecominds Press, 2025)
The article analyzes the problems of using digital technologies both in the republic and abroad. It also examines the tools of the Chinese digitalization model.
Keywords: Digital transformation, transport, innovation, investment, transport infrastructure, freight transportation, commodity markets, competitiveness, infrastructure projects.